2005
DOI: 10.1007/s00125-005-1773-8
|View full text |Cite
|
Sign up to set email alerts
|

Normal metabolism of apolipoprotein B100-containing lipoproteins despite qualitative abnormalities in type 1 diabetic men

Abstract: Aims/hypothesis: Type 1 diabetic subjects are at increased risk of cardiovascular disease and exhibit multiple qualitative abnormalities of apolipoprotein (apo) B100-containing lipoproteins. This stable isotope kinetic experiment was designed to study whether these abnormalities are associated with changes in the synthesis and fractional catabolic rates of VLDL-, IDL-and LDLapoB100. Methods: Using a bolus followed by a 16-h constant infusion of 13 C-leucine, we performed a kinetic study in eight men with type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The major factor contributing to the bias we observed in the calculated LDL‐C is the estimation of VLDL‐C from total serum triglyceride, which is intrinsic to the Friedewald calculation. The cholesterol in VLDL is estimated as total triglyceride/2.2 (in mmol/l), but in these young adults with largely favourable lipid profiles we found that 48% of triglyceride is present in HDL and LDL (Table 1) in agreement with other reports in Type 1 diabetes and healthy subjects [25]. Indeed, the contribution of VLDL‐C calculated from this non‐VLDL triglyceride would be 0.20 mmol/l (averaging the two populations), accounting for the difference in LDL‐C estimates not as a result of the difference in HDL‐C.…”
Section: Discussionsupporting
confidence: 92%
“…The major factor contributing to the bias we observed in the calculated LDL‐C is the estimation of VLDL‐C from total serum triglyceride, which is intrinsic to the Friedewald calculation. The cholesterol in VLDL is estimated as total triglyceride/2.2 (in mmol/l), but in these young adults with largely favourable lipid profiles we found that 48% of triglyceride is present in HDL and LDL (Table 1) in agreement with other reports in Type 1 diabetes and healthy subjects [25]. Indeed, the contribution of VLDL‐C calculated from this non‐VLDL triglyceride would be 0.20 mmol/l (averaging the two populations), accounting for the difference in LDL‐C estimates not as a result of the difference in HDL‐C.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the considerable amount of studies in type 2 diabetes and the metabolic syndrome comparably little is known on the metabolism of lipoproteins in type 1 diabetes. Lipid profiles in well‐controlled subjects with type 1 diabetes tend to be similar to those seen in nondiabetic controls but altered lipoprotein composition has consistently been demonstrated despite normal lipoprotein metabolism in these subjects [26, 27]. The finding of an increased secretion of triglyceride‐rich VLDL associated with an increased number of small‐dense LDL particles – a constellation known to be highly prevalent in premature coronary artery disease in nondiabetic subjects as well as in type 2 diabetes [4, 40, 41] – was also suggested to be associated with accelerated atherosclerosis in type 1 diabetes [27].…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidaemia is a well‐established cardiovascular risk factor in the general population and in subjects with type 2 diabetes. It has been suggested to contribute to the increased risk in subjects with type 1 diabetes as well [26, 27]. However, epidemiological data have indicated a stronger association of apo B with microvascular complications than with cardiovascular disease in type 1 diabetes [28–30].…”
Section: Introductionmentioning
confidence: 99%
“…The hypotheses proposed to explain the occurrence of hepatic steatosis in Type 1 diabetes in humans were atypical lipoprotein ratios and/or atypical lipoprotein function leading to insufficient triglyceride secretion from the liver by Very-Low Density Lipoprotein and increased hepatic lipogenesis [6]. However, we previously showed in an apolipoprotein B kinetic study that despite qualitative abnormalities, the metabolism of apoB100-containing lipoproteins was not altered in patients with Type 1 diabetes [9].…”
Section: Introductionmentioning
confidence: 94%